Resistance of Streptomyces spp. Isolates towards Active Ingredients of the Nematicide Carbofuran and Dazomet, and its Effect on the Mortality of Nematodes Meloidogyne spp. - Siti Fatimatus Syahrok; Penta Suryaminarsih; Sri Wiyatiningsih (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The decrease in tomato plant production is caused by pest and disease attacks, one of which is the nematode Meloidogyne spp. Control measures still rely on synthetic nematicides, which can have negative effects on health, a broad spectrum of impact, microbial diversity, and resistance to attacks by Meloidogyne spp. Therefore, alternative control using biological agents that are resistant to the active ingredients of nematicides (carbofuran and dazomet) and have the ability to inhibit attacks by Meloidogyne spp. is needed. This study aims to test the resistance of Streptomyces spp. isolates to the active ingredients of synthetic nematicides, carbofuran and dazomet, and evaluate their effect on the mortality of Meloidogyne spp. nematodes. The method used is in vitro with the poisoned food technique and nematicidal activity testing against juvenile nematodes. The results show that the TMP isolate has better resistance than SP against carbofuran, with the second highest colony count of 11.47 × 10⁶ CFU/ml. Meanwhile, dazomet significantly inhibited the growth of Streptomyces spp. colonies. The mortality test showed that the TMP isolate was able to achieve a mortality rate of 59.01% in Meloidogyne spp. This proves the potential of Streptomyces spp. as a biological agent in nematode control and its resistance to nematicide residue active ingredients, making it an environmentally friendly alternative in agricultural practices. Keywords: Biological agent, Carbofuran, Dazomet, Meloidogyne spp., Streptomyces spp.